Lincoln : a photobiography - Freedman, Russell, 1929-2018.; Alfred Whital Stern Collection of Lincolniana (Library of Congress) (New York, N.Y. : Clarion Books, 1987)
Photographs and text trace the life of the Civil War President.
Includes index.
Bibliography: p. 142-143.
Keywords: Lincoln, Abraham, -- 1809-1865 -- Juvenile literature; Lincoln, Abraham, -- 1809-1865.; Presidents -- United States -- Biography -- Juvenile literature; Presidents; Newbery Medal